Penerapan Bahan Ajar PAI Berbasis Model Cooperative Learning Untuk Meningkatkan Hasil Belajar Siswa Di SMA Al-Azhar Menganti Gresik - El-Yunusi, Muhammad Yusron Maulana; Irawan, Alfiatul Izzati; Safitri, Shinta Maulidia; Noviyanti, Derisma Vita (LP3M STIT Al Urwatul Wutsqo Jombang, 2023)
The purpose of this study was to find out how the application of PAI learning materials with cooperative learning models on student learning outcomes. This study uses a qualitative approach with a case study type of research. Methods of data collection is done by using interviews, observation, and documentation. Data analysis was carried out through the stages of data reduction, data display, and verification as well as drawing conclusions. Data validity test was carried out using the triangulation method. The results of the study show that (1) the cooperative learning method can improve student learning outcomes, (2) there are several preparations in applying the cooperative learning method to teaching and learning activities in class, starting with planning by identifying the level of student intelligence, implementation by forming groups small, and evaluation of learning outcomes, (3) the teacher's efforts to design learning more creatively greatly affect the success rate of applying the cooperative learning method, (4) there are many advantages than disadvantages when the cooperative learning method is applied to high school students.